Persepsi Terhadap Nikah Sirri Kasus Masyarakat Desa Sinarrancang, Kecamatan Mundu, Kabupaten Cirebon - Ismail Zubir (Balai Penelitian dan Pengembangan Agama Semarang, 2011)
This study aims to find out the perception of people in Sinarrancang, Mundu, Cirebon, West Java, on nikah sirri (“secret” marriage). Using qualitative approach the study reveals that in their opinion nikah sirri mean nikah “kyai”, it is a marriage by ulama and has become a long hereditary tradition. According to fiqih munakahat (a branch of Islamic law which studies about marriage) this kind of marriage is legitimate because it meets the conditions and requirements of marriage. According to positive law, however, such marriage is illegal for not being registered at KUA (a governmental institution which administers Muslim marriage). In order to change their perception on nikah sirri, it needs to socialize UU No. 1 Tahun 1974 continuously. KUA’s service to people has to be addressed so that its accountability and responsibility could run effectively; and more importantly the draft of Religious Courts Law Materials that would provide punishment for those conducting nikah sirri do not contradict with Islamic law.